2015
DOI: 10.1017/s0007114515000690
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of vitamin C is tissue specific with early saturation of the brain and adrenal glands following differential oral dose regimens in guinea pigs

Abstract: Vitamin C (VitC) deficiency is surprisingly common in humans even in developed parts of the world. The micronutrient has several established functions in the brain; however, the consequences of its deficiency are not well characterised. To elucidate the effects of VitC deficiency on the brain, increased knowledge about the distribution of VitC to the brain and within different brain regions after varying dietary concentrations is needed. In the present study, guinea pigs (like humans lacking the ability to syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 87 publications
(109 reference statements)
3
50
0
Order By: Relevance
“…The capacity of the brain to hold on to vitamin C is widely acknowledged [32] , [33] , [34] and our confirmatory finding supports the physiological relevance of the data. Moreover, we recently reported that saturation of the brain occurs faster than for most other tissues [35] . It can also be extracted from Fig.…”
Section: Discussionmentioning
confidence: 95%
“…The capacity of the brain to hold on to vitamin C is widely acknowledged [32] , [33] , [34] and our confirmatory finding supports the physiological relevance of the data. Moreover, we recently reported that saturation of the brain occurs faster than for most other tissues [35] . It can also be extracted from Fig.…”
Section: Discussionmentioning
confidence: 95%
“…Food intake in each group was estimated daily by weighing feed-remains prior to refill. After either 16 or 25 weeks, guinea pigs were semi-fasted over-night (no feed, but access to hay), pre-anaeshetized with 0.08 ml/kg BW Zoletil-mix, placed on isoflurane and euthanized by decapitation following an intra-cardial blood sample as previously described [ 11 , 17 ]. Organs were rapidly collected, rinsed in phosphate buffered saline, weighed and stored at −80 °C or in paraformaldehyde for histological examinations.…”
Section: Methodsmentioning
confidence: 99%
“…These transporters are high affinity transporters that are capable of maintaining a many fold higher intracellular concentration of vitamin C compared to plasma even during periods of reduced intake (reviewed in (Lindblad, Tveden-Nyborg, and Lykkesfeldt 2013)). As studied in detail in guinea pigs, that like humans do not have the ability to biosynthesize vitamin C, the brain is a particularly relevant example as it has a very high vitamin C content and a high preference in the systemic homeostasis of vitamin C (Hasselholt, Tveden-Nyborg, and Lykkesfeldt 2015;Frikke-Schmidt et al 2011). Such deep compartments do not equilibrate rapidly with blood and other compartments and are therefore not assessed in shortterm isotope dilution experiments such as those conducted by Kallner and others.…”
Section: Prevention Of Scurvymentioning
confidence: 99%